Out of the box: behaviourism and the mangle of practice. Issue 1 (2nd January 2019) - Saari, Antti
ABSTRACT: Although often labelled obsolete and ethically dubious, twentieth-century behaviourist principles of learning have been central to the development of instructional technology and the design of modern learning environments. Using Andrew Pickering's philosophy, this article addresses behaviourism as a mangle of practice to highlight the conceptual and non-human agency involved in research on learning, and to analyse how these forms of agency allow scientific knowledge to travel from experimental research settings to teaching.